Introductory probability and statistical applications Ed 2 - Paul L Meyer (New Delhi Oxford and IBH Publishing Co. Pvt. Ltd., 1970)
Introduction to probability -- Finite sample spaces -- Conditional probability and independence -- One-dimensional random variables -- Functions of random variables -- Two- and higher-dimensional random variables -- Further characterization of random variables -- The Poisson and other discrete random variables -- Some important continuous random variables -- The moment-generating function -- Applications to reliability theory -- Sums of random variables -- Samples and sampling distributions -- Estimation of parameters -- Testing hypothesis -- Appendix -- Answers to selected problems
Keywords: Reliability Theory; Random Vairables; Testing Hypotheses